Bimbingan Kegiatan Pembiasaan Keagamaan Dalam Meningkatkan Hasil Ujian Praktek PAI di SDN Perumnas 1 Subang - Muiz Fahmi Septiana; Tri hendri herdiansyah; Ayi Najmul Hidayat; Ulfah (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M) STAI, 2024)
This study aims to determine the influence of religious habituation activities on improving the results of Islamic Education (PAI) practice exams at SDN Perumnas 1 Subang. The research method used is a quantitative approach with a quasi-experimental design. The research sample consists of sixth-grade students selected randomly. The research instruments include a PAI practice test and observation sheets to measure the intensity and involvement of students in religious habituation activities. The results of the study show a significant improvement in the PAI practice exam results in the group of students who received guidance on religious habituation activities compared to the control group. This guidance has proven effective in forming consistent worship habits and enhancing students' understanding and skills in performing religious practices. The implications of this study highlight the importance of integrating religious habituation activities into the school curriculum to support the improvement of PAI learning outcomes.